Development and interaction of disturbance waves in downward annular gas-liquid flow. (May 2021) - Cherdantsev, Mikhail V.; Isaenkov, Sergey V.; Cherdantsev, Andrey V.; Markovich, Dmitry M.
Highlights: Development of downward annular flow in 11.7 mm pipe over the first 400 mm is studied using BBLIF technique. Strong change in wave and flow properties is found 15 pipe diameters from the inlet. Wave amplitude and entrained fraction keep growing beyond this point. An average surviving disturbance wave absorbs two other waves in process of its evolution. Effect of coalescence on wave speed and height is small in comparison to that of wave evolution. Abstract: The behavior of the disturbance waves is studied in downward adiabatic air-water annular flow in a vertical pipe with an inner diameter of 11.7 mm. The range of liquid wetting densities is 2.5–4.6 cm 2 /s and the range of superficial gas velocities is 22–57 m/s. The paper is focused on the downstream evolution of the main properties of individual disturbance waves at the stage of flow development along with the process of coalescence of disturbance waves. Brightness-based laser-induced fluorescence technique enabled us to obtain spatiotemporal matrices of the local instantaneous thickness of liquid film along one longitudinal section of the pipe with a length of 400 mm. Dependencies of the main characteristics of the flow on the downstream distance are analyzed. Local shear stress, base film thickness, and longitudinal size of the disturbance waves are stabilized at the distance of 150–200 mm below the inlet. Disturbance wave velocity increases strongly up to this point; further downstream, the acceleration is reduced significantly. Disturbance wave amplitude grows approximately as the square root of distance within the whole region of interrogation. Entrained fraction grows linearly within this region. Disturbance wave frequency decreases exponentially due to the coalescence. It is found that an average disturbance wave surviving through the development stage absorbs two other waves. Individual acts of coalescence of disturbance waves are analyzed quantitatively to investigate their contribution to the change of disturbance wave properties. On average, when a disturbance wave absorbs another one, its speed increases by 2%, its amplitude – by 5–6% and its longitudinal size remains the same. Thus, the disturbance wave properties change downstream mainly due to their individual evolution, not due to coalescence.